The Development of Palm Sugar Enterprises in Improving the Welfare of the Community in Lombo Village, Pitu Riase Subdistrict, Sidenreng Rappang Regency - Fitriani; Bahruddin; Fajar Ladung; Sofyan; Fitriyani Syukri (IECON: International Economics and Business Conference, 2025)
This study aims to determine the development of ant sugar business in improving the welfare of the people of Lombo Village, Pitu Riase District, Sidenreng Rappang Regency and to determine the effect of the development of ant sugar business in improving the welfare of the people of Lombo Village, Pitu Riase District, Sidenreng Rappang Regency. The data collection techniques used in this study are observation, interviews and documentation. Informants in this study were ant sugar entrepreneurs, workers and surrounding residents. Data analysis techniques used in qualitative research consist of data collection, data reduction, data presentation and drawing conclusions. The results showed that the development of this palm sugar production business still uses traditional production tools and a limited number of workers. This simplicity is also seen in terms of marketing and distribution, which are only around the Sidenreng Rappang district. The presence of the palm sugar production business in Lombo Village has an influence on the socio-economic life of the people in Lombo Village and its surroundings. In terms of the economy, the production of ant sugar encourages job creation. The opening of employment opportunities absorbs labor and also causes an increase in people's income.